Carbon dioxide absorption kinetics in potassium threonate - A. F. Portugal (2008)
The absorption of carbon dioxide in potassium threonate aqueous solutions is studied at concentrations ranging from 0.1 to 3 M and temperatures from 293 to 313 K. This study includes experimental density, viscosity, solubility of N2O and absorption kinetics of CO2 (using a stirred cell reactor) data obtained for the various potassium threonate solutions. The diffusion coefficients Of CO2 and potassium threonate in the absorption solutions are estimated using a modified Stokes-Einstein relation. N2O solubility is interpreted using the Schumpe [1993. The estimation of gas solubilities in salt-solutions. Chemical Engineering Science 48(1), 153-158] model and CO2 physical solubility estimated. Physical absorption experiments were performed in the stirred cell in order to determine the physical mass transfer coefficients. The kinetics results are interpreted using both the pseudo-first-order and the DeCoursey approaches. It was concluded that CO2 absorption in the aqueous potassium threonate solutions is well represented by -r(CO2) = 4.13 x 10(8) exp (-3580/T) C-S exp(0.90C(S))C-CO2